THE USE OF METAPHOR IN POLITICAL DISCOURSE: A COGNITIVE LINGUISTIC APPROACH (The Role of Exact Sciences in the Era of Modern Development, 2025)
This paper delves into the significant role metaphor plays in shaping political discourse through a cognitive linguistic lens. Metaphors are not merely decorative tools but serve as fundamental cognitive mechanisms through which political realities are constructed, understood, and communicated. Drawing on the conceptual metaphor theory developed by George Lakoff and Mark Johnson, the paper analyzes how certain metaphors become dominant in political narratives, guiding public perception and influencing decision-making. Through a qualitative analysis of contemporary political speeches and media texts, this study identifies recurring metaphorical frameworks—such as war, family, and journey metaphors—and explores how these metaphors subtly shape ideological positions and emotional responses. The findings suggest that metaphors in political language are instrumental in simplifying complex issues, mobilizing support, and framing adversaries, revealing their power to shape both thought and action in political contexts.